Propostas para a elaboração de plano de gestão para a praia de Macapá - Luis Correia - PI - Rocha, Glairton Cardoso [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The coastal environments are remarkably dynamic responding to changes in a much greater speed than other environmental units within the continent, thus, they are sensible to changes caused by humans leading to unwanted consequences. One of the ways to avoid negative impacts is through planning and coastal management that to optimize the results should be developed in a participatory perspective and consider the dynamic characteristics of the local environment. The study area includes the Macapá beach in the city of Luis Correia, state of Piaui, which belongs to the Microregion of the lower Parnaíba. Thus the present study aims to develop a participatory management plan appropriate to the peculiarities of local natural dynamics. For this purpose, we attempted to understand the natural dynamics by making use of the systemic approach, aided techniques by the Australian School of Oceanography. The consultation was carried out to the population through questionnaires, In order to assess the environmental quality and equipment of infrastructure, and allows identification of strengths and limitations of use, and social order problems and environmental

Os ambientes costeiros são notadamente dinâmicos respondendo a alterações numa velocidade muito maior que outras unidades ambientais no interior do continente. Desta forma, são sensíveis às modificações provocadas pelo homem, podendo levar a consequências indesejadas. Uma das formas de evitar efeitos negativos é através do planejamento e da gestão costeira. Para otimizar os resultados, a gestão deve ser desenvolvida sob uma ótica participativa e considerar as características da dinâmica ambiental local. A área de estudos compreende a praia de Macapá, no município de Luís Correia, estado do Piauí, que pertence à Microrregião do Baixo Parnaíba Piauiense. Assim, o presente trabalho tem por objetivo geral apresentar propostas para elaboração de plano de gestão. Para essa finalidade foi necessário compreender a dinâmica natural, além de consultar a população por meio de questionários. As técnicas de pesquisa permitiram avaliar a qualidade ambiental e dos equipamentos de infraestrutura, além de auxiliar na identificação de potencialidades e limitações de uso, bem como identificar problemas de ordem socioambiental
Keywords: Physical geography - Environmental aspects; Geografia física - Aspectos ambientais; Geografia ambiental; Gerenciamento costeiro; Política ambiental; Qualidade ambiental; Direito ambiental; Piaui